Arranging coil winding circuits of synchronous permanent-magnet machines on rotor - Smirnov, Alexander; Dar’enkov, Andrey; Kryukov, Evgeny (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Methodology of constructing coil winding electrical circuits for salient-pole stator of electrical permanent-magnet machines on the rotor is proposed, which is based on the required number of pole pairs (synchronous speed) and the number of phases. The methodology algorithm is based on determining the value of the number of stator teeth as the closest to the number of rotor poles number value, multiple of phase number, which provides a sufficient level of pitch coefficient and winding coefficient. The algorithm was tested by several examples of constructing synchronous machines winding circuits, known from electrical engineering theory and practice, including mass-produced ones. In all the examples, if the proposed methodology guidelines were formally and strictly followed, the correct circuit designs came out as a result. For high power motor pilot design, one and the same machine design variants were compared, having thirty six slots on stator, three-phase and nine-phase windings, synthesized according to the proposed algorithm for thirty two-pole rotor. Engine torque calculation with both circuit options performed by finite elements method showed the nine-phase winding developed torque advantage by 20%, due to less discretion of MMF slot distribution.